2021
DOI: 10.3390/ijerph18020625
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the Family Functioning of Individuals with Drug Addiction and Relapse Tendency: A Moderated Mediation Model

Abstract: To explore the relationship between family functioning, psychological capital, life history strategy, and relapse tendency of individuals with drug addiction, 842 individuals with drug addiction completed a questionnaire. The results showed that (1) there was a significant negative correlation between the family functioning of individuals with drug addiction and their relapse tendency; (2) psychological capital played an intermediary role between family functioning and relapse tendency; and (3) life history st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 66 publications
2
21
1
3
Order By: Relevance
“…Furthermore, they found that the relationship problems with family members and girlfriends are also a source of recurring behaviour. The findings of this study are in line with the findings of a study conducted by Zeng and Tan (2021), suggest that family members should collaborate with drug addiction treatment centres and participate in the education and treatment process to help reduce drug relapse. The institution of the family is closely related to the self.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, they found that the relationship problems with family members and girlfriends are also a source of recurring behaviour. The findings of this study are in line with the findings of a study conducted by Zeng and Tan (2021), suggest that family members should collaborate with drug addiction treatment centres and participate in the education and treatment process to help reduce drug relapse. The institution of the family is closely related to the self.…”
Section: Discussionsupporting
confidence: 87%
“…In the context of addictions, dysfunctional family functioning is frequently found in subjects with alcohol and substance abuse [45,46] and with behavioural addictions, such as gambling disorder [47], problematic smartphone use [48], Internet addiction [49], as well as compulsive shopping [50]. Furthermore, recent evidence showed a negative correlation between the family functioning of individuals with drug addiction and their relapse tendency [51], supporting the importance of family collaboration during the treatment process [52].…”
Section: Introductionmentioning
confidence: 99%
“…It can therefore be argued that living in an intimate family environment with parents who have proper supervision and control over their youth can help the children stay away from drug use and addiction, and thus, students who live with their family consume less drugs and alcohol. 33,34 This study also showed that aggression is significantly related to history of drug use among family, friends, and to socialisation with addicts, while other studies reported 35,36 married, smoker students 37 and at lower levels of education. 36 Compared with our study, it can be said that this lack of consistency may be justified by noting how older age and higher academic degrees increase the individual's awareness of his behaviours and consequently his control over them and make him show less unreasonable behaviours in stressful situations.…”
Section: Discussionmentioning
confidence: 49%